Bridging the Gap Interfaith Competence as a National Security Strategy in Multireligious Indonesia – Perspectives from Christian Educators - Roce Marsaulina; Gilbert Timothy Majesty (International Perspectives in Christian Education and Philosophy, 2025)
This qualitative study addresses the critical gap between religious diversity and national security in Indonesia by proposing interfaith competence as a strategic imperative. Situated within a constructivist framework, the research investigates the perspectives of Christian educators, positing that their unique position at the intersection of faith formation and pedagogy offers invaluable insights into building sustainable religious harmony. Constructivism provides the analytical lens, emphasizing that understandings of religious "others," security threats, and peaceful coexistence are socially constructed through discourse, experience, and education. Therefore, the development of interfaith competence is not merely an ethical goal but a active process of constructing a shared societal reality resilient to sectarian conflict. The primary objective of this research is to explore how Christian educators conceptualize, practice, and perceive their role in fostering interfaith competence as a contribution to Indonesia's national security architecture. Data was gathered through in-depth interviews and thematic analysis was employed to identify recurring patterns and nuanced understandings. The findings reveal that these educators view interfaith competence comprising affective, cognitive, and behavioral dimensions as a vital tool for deconstructing prejudice and building social cohesion. They position their educational practices as essential for shaping citizens who can navigate a multireligious society, thereby mitigating the risks of radicalization and conflict that threaten national integrity. The study concludes that integrating interfaith competence, as articulated by these grassroots actors, into broader national policy offers a proactive, soft-power strategy for safeguarding Indonesia's security, moving beyond purely military or political approaches to foster a collectively constructed resilience.